Investigation on carbon nanotube oxide for anhydrous proton exchange membranes application. Issue 26 (17th December 2019) - Pan, Bin; Jia, Tingting; Duan, Xiangqing; Zhong, Zhixuan; Bai, Guosheng; Che, Quantong
ABSTRACT: The widespread participation of polymers in the membrane preparation has been considering to be critical for the development of proton exchange membranes (PEMs). For the polymers without functional groups to conduct protons, the introduction of proton conduction carriers with the formation of composite membranes is an effective strategy to prepare PEMs with the outstanding proton conductivity. However, there remains a potential risk of the components leaking from composite membranes due to the lack of the interaction force. Here, the composite of carbon nanotube oxide (OCNT) assembling with cadmium telluride (CdTe) and 1‐butyl‐3‐methylimidazolium hexafluorophosphate (bmimPF6 ) was introduced into the system of phosphoric acid (PA) doping poly(vinylidene fluoride) (PVDF) with the formation of PVDF/OCNT‐CdTe‐bmimPF6 /85%PA membranes. PA molecules are anchored by the inorganics of OCNT‐CdTe‐bmimPF6 and are stabilized in membranes. The high and stable proton conductivity values at the elevated temperature are obtained comparing the reported PVDF/bmimPF6 /PA membranes. Specifically, the proton conductivity value reached 1.28 × 10 −1 S/cm at 160 °C and the value is stable 1.70 × 10 −2 S/cm at 120 °C lasting for 350 h. The fine stability in components could make the membranes extricate from the predicament of proton conductivity decline exceeding 120 °C under anhydrous conditions in PVDF/bmimPF6 /PA membranes. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48833. Abstract :